2021
DOI: 10.1080/09500693.2021.1928326
|View full text |Cite
|
Sign up to set email alerts
|

Species identification skills in teacher education students: the role of attitude, context and experience

Abstract: Knowledge about local species and a positive attitude towards all living organisms are important to motivate the next generations to protect biodiversity. We compared local species identification skills and declared attitude towards invertebrates across genders in Italian and Norwegian students in teacher education. We focused on Norway and Italy for this comparative study, because of their different teaching traditions and relationships with outdoor education. We found a significant difference in local specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
(73 reference statements)
0
6
0
3
Order By: Relevance
“…More than virtual fieldwork experience, video games such as Animal Crossing could bring natural virtual experiences for children who live mostly in urbanized environment. Melis et al (2021) have found a positive correlation between the ability to identify species and the interest toward these species in a survey in Italy and Norway. As shown by our results, playing AC could enhance players' ability to recognize the in‐game species (cartoonized and pixelated) from a real picture of the organism and, thus, to obtain significantly better scores at the naturalistic survey than nonplayers.…”
Section: Discussionmentioning
confidence: 99%
“…More than virtual fieldwork experience, video games such as Animal Crossing could bring natural virtual experiences for children who live mostly in urbanized environment. Melis et al (2021) have found a positive correlation between the ability to identify species and the interest toward these species in a survey in Italy and Norway. As shown by our results, playing AC could enhance players' ability to recognize the in‐game species (cartoonized and pixelated) from a real picture of the organism and, thus, to obtain significantly better scores at the naturalistic survey than nonplayers.…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that children have negative attitudes to invertebrates when you look at the values of their teachers. An evaluation of students in teacher education in Norway and Italy showed that there were negative attitudes toward invertebrates, especially in Italy and much more in females [ 23 ]. This gender gap is worrying, as early education teachers are predominantly female, and prejudices learned early are hard to counter.…”
Section: We Do Not Like or Value The Invertebrates That We Do Know Aboutmentioning
confidence: 99%
“…Guru berperan penting dalam merancang strategi pembelajaran yang tepat sesuai tujuan (Chalkiadaki, A, 2018). Guru berperan penting mengembangkan keterampilan 4C dalam proses pembelajaran (Chalkiadaki, A, 2018;Melis, C et al, 2021;Tindowen, D. J. C et al;2017).…”
Section: Pendahuluanunclassified